INTEGRASI NILAI-NILAI CINTA DALAM PEMBELAJARAN PAI BERBASIS KITAB KUNING - Siti Muntiasih; Vina Yunika Fitriani; Salmah Fa’atin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the integration of love values into Islamic education based on the yellow book at MI Roudlotul Mubtadiin Balekambang Jepara. Amidst the trend of education digitization, this love-based curriculum emphasizes the values of compassion, empathy, and humanity as the foundation of learning. The purpose of this study is to identify the application of love values in PAI learning, as well as the supporting and inhibiting factors and their influence on student understanding. The descriptive qualitative approach and data collection techniques through observation, in-depth interviews, and documentation review show that the integration of love values in PAI learning through the study of classical Islamic texts is appropriate and successful in improving student competence and religious character in PAI learning. However, the main obstacles are the weak competence of educators in mastering modern pedagogy and the limited time in the formal curriculum, which pose challenges for institutions. The researcher concludes that the integration of values in the Love-Based Curriculum for PAI learning can be effective with the adoption of a religious culture from the pesantren environment, namely through the study of classical Islamic texts.